PENYUTRADARAAN DENGAN GAYA OBSERVASIONAL PADA DOKUMENTER BIOGRAFI “TEGUH ING PANGURIPAN” DI SLEMAN - Nindia Aprilia; Oktafiani Herlina; Antonius Janu Haryono (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACT The documentary work entitled Teguh Ing Panguripan is a documentary program that tells the profile of Teguh Rahardjo. Here he is deaf and speech impaired, but in his life he can still live normally both at work and interacting with other people. The life he lives certainly has various obstacles and problems, but his family and the people around him are able to help him in his life. The title of this work has a meaning that reflects the character, namely "Teguh" which is taken from the character's first name and "Ing panguripan" has a meaning in the life that Mas Teguh is living. Observational style documentaries are films that refuse to intervene in objects and events. They try to be neutral and not judge the subject or event. To create an observational documentary, it takes a lot of time and research so that you can understand the daily lives of the characters. Therefore, the author does not intervene excessively in the subject. In making this documentary, the director focuses on the subject's daily life and the communication process carried out. In making this documentary work, the director uses an observational directing style with the aim of being able to show the lives of the characters and produce natural work, because in this documentary style it is not artificial and corresponds to reality. This Integrated Practicum work is packaged in a duration of 24 minutes including bumper, clapper and credit title. This work has a message for the audience, namely about deaf and speech impaired people who are still fighting for their dream of being able to build a house and also live a normal life with the people around them. It is hoped that this work will provide lessons for writers if they also create similar works in the future. The author pays more attention to the plot of the story and the subject, because if you look at the directing style used and the subject, it is fundamentally unpredictable and has to be studied for a long time. Keywords: Documentary, Director, Observational, Teguh Rahardjo, Teguh Ing Panguripan.